2014
DOI: 10.1039/c4cp01798f
|View full text |Cite
|
Sign up to set email alerts
|

Determination of protein binding affinities within hydrogel-based molecularly imprinted polymers (HydroMIPs)

Abstract: Hydrogel-based molecularly imprinted polymers (HydroMIPs) were prepared for several proteins (haemoglobin, myoglobin and catalase) using a family of acrylamide-based monomers. Protein affinity towards the HydroMIPs was investigated under equilibrium conditions and over a range of concentrations using specific binding with Hill slope saturation profiles. We report HydroMIP binding affinities, in terms of equilibrium dissociation constants (Kd) within the micro-molar range (25 ± 4 μM, 44 ± 3 μM, 17 ± 2 μM for ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…The resultant population of imprinted sites would therefore contain some cavities that are associated with protein clusters. This phenomenon is supported by our previous work[34,35], where force spectroscopy analysis of MIPs suggested that the cavities accommodated an agglomeration of template protein molecules rather than just a single molecule. It is therefore possible that the solution phase represents a more dispersed protein population compared with the original imprinted template population for rebinding protein at low concentrations.…”
supporting
confidence: 78%
“…The resultant population of imprinted sites would therefore contain some cavities that are associated with protein clusters. This phenomenon is supported by our previous work[34,35], where force spectroscopy analysis of MIPs suggested that the cavities accommodated an agglomeration of template protein molecules rather than just a single molecule. It is therefore possible that the solution phase represents a more dispersed protein population compared with the original imprinted template population for rebinding protein at low concentrations.…”
supporting
confidence: 78%
“…Along with water solubility, low cost, easy production and engineering are some of polyacrylamide gels’ attractive properties concerning molecular imprinting [46]. Studies on polyacrylamide hydrogel-based MIPs have demonstrated sensitivity and selectivity towards several proteins with different biological roles, sizes and electrochemical activities, namely haemoglobin, myoglobin, cytochrome c, bovine serum albumin (BSA) and catalase [47,48,49]. Further improvements in terms of MIP selectivity have been attempted by including a metal chelating complex comprising bifunctional vinyl groups with the ability to co-polymerize within the polyacrylamide matrix [50].…”
Section: Polymeric Materialsmentioning
confidence: 99%
“…In this sense, measurement methods where one of the molecules is immobilized, such as SPR and QCM, may best emulate the release conditions if the method of attachment is the same (30). Other methods include indirect measurement of binding constants by fitting experimental data to adsorption or diffusion models for molecules within the gel (31). For example, the binding constant for a protein immobilized to a gel was measured by observing the diffusion of its binding partner after wetstamping it on specific sites on the gel surface (32).…”
Section: Characterizing Binding Partners For Affinity-controlled Releasementioning
confidence: 98%